Pengaruh Dividen Policy, Liquidity, Profitability dan Company Size pada Debt Policy dengan Financial Performance sebagai variabel intervening - Septiani, Ni Kadek Errika Sindy (IPM2KPE, 2025)
This study aims to analyze the influence of dividend policy, liquidity, profitability, and firm size on debt policy, with financial performance as an intervening variable, in technology companies listed on the Indonesia Stock Exchange for the 2019–2023 period. This study uses a quantitative approach with path analysis and data processing using SPSS on 60 observations from 12 companies. The results show that only liquidity has a significant direct effect on debt policy, while dividend policy, profitability, and firm size do not. However, all independent variables have a significant indirect effect on debt policy through financial performance as an intervening variable. These findings support the perspectives of agency theory, trade-off theory, and pecking order theory in explaining the relationships between variables in the financial structure of technology companies. Keywords: Dividend Policy, Liquidity, Profitability, Firm Size, Debt Policy